MODEL KURIKULUM MILLER-SELLER DAN PENGEMBANGANNYA DALAM INSTRUCTIONAL DESIGN - Syafruddin Nurdin (IAIN Batusangkar, 2016)
In order to curriculum can be implemented as well as in classroom lecture, therefore a syllabus should be developed become instructional design. Instructional design containt of components; standard competence, basic of competence, indicator of competence, subject of lecture, and it’s materials, learning experience (teaching and learning strategy), media, evaluation, and reference. Instructional design is activity projection that will be done by lecturer in learning activity.Key Words: Model Kurikulum, Miller-Seller, pengambangan, instructional design.